Plataforma para análise da deformação de uma viga simplesmente engastada - Santos, Mara Alice Batista dos (Universidade Federal Rural do Semi-Árido, 2018)
The considerable growth in the infrastructures market promoted even more the beams visibility and application. However, linked to this ascention is the preoccupation with the deformations that are caused to it. Knowing this, the work is about the use of an experimental platform, where it has a stainless steel beam, simply embed in order to promote the obtainment of these values of deformations next to the extensometers of electrical resistance. The platform was built by a rapid prototyping machine (3D printer) consisting of polymer material. The extensometers were chosen because they have as main advantages a high level of precision when compared to other sensors, in addition to their cost benefit. These, in it turns were fixed on the beam (upper and lower face). The necessary parameters to get the deformation value were acquired through the data acquisition system, applied to the four wires method (4) and the Wheatstone bridge circuit, respectively. This way, the results were obtained by tests and the theoretical calculation, that were compared in order to prove the experimental data veracity, making possible the identification of elasticity modulus of the beam.
Monografia
Keywords: Plataforma experimental; Deformação; Extensômetro de resistência elétrica; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA